amendment to Misdemeanour Code concerning offences against security and order in traffic (Ius Novum, 2022)
Due to the amendment, which entered into force on January 1, 2022, a number of provisionsin Chapter XI of Misdemeanour Code concerning safety and order in communication weresignificantly changed. The legislator decided to introduce new types of prohibited actsand significantly increased the amount of the fine for certain offenses. These changes arerevolutionary, which is also associated with controversy. This is because some of the changesmade raise doubts due to the higher degree of their repression, which makes the punishabilityof certain offenses disproportionate in relation to similar crimes under the Penal Code. Thisissue will be presented later in the article.
Keywords: misdemeanour; prohibited act; social harmfulness; light traffic accident; fine